2022
DOI: 10.3389/fnhum.2022.831995
|View full text |Cite|
|
Sign up to set email alerts
|

Neurofeedback Training of Alpha Relative Power Improves the Performance of Motor Imagery Brain-Computer Interface

Abstract: Significant variation in performance in motor imagery (MI) tasks impedes their wide adoption for brain-computer interface (BCI) applications. Previous researchers have found that resting-state alpha-band power is positively correlated with MI-BCI performance. In this study, we designed a neurofeedback training (NFT) protocol based on the up-regulation of the alpha band relative power (RP) to investigate its effect on MI-BCI performance. The principal finding of this study is that alpha NFT could successfully h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…These alterations mirror were also observed during actual motor tasks, suggesting functional equivalence in brain engagement when a subject performs a same imagined and actual movement [3], [10]. This phenomenon highlights the potential of VNFB to enhance plasticity in neuromotor mechanisms, suggesting its relevance for rehabilitation strategies especially addressed to individuals with severe motor impairments because of a SCI or other causes [11].…”
mentioning
confidence: 55%
“…These alterations mirror were also observed during actual motor tasks, suggesting functional equivalence in brain engagement when a subject performs a same imagined and actual movement [3], [10]. This phenomenon highlights the potential of VNFB to enhance plasticity in neuromotor mechanisms, suggesting its relevance for rehabilitation strategies especially addressed to individuals with severe motor impairments because of a SCI or other causes [11].…”
mentioning
confidence: 55%
“…Future BCIs driven by alpha wave modulation could account for an individual's neurophysiology by, for example, selecting subject-specific frequency bands, a method commonly used in MI-BCI [61][62][63] to optimize classification. Ultimately, users may also benefit from neurofeedback training protocols, such as the one proposed in Zhou et al [64], which have been shown to successfully help increase alpha power.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%